Manajemen Pekarangan Ramah Lebah Tanpa Sengat sebagai Upaya Peningkatan Jasa Lanskap Perkotaan - Nafidzah Qisthina; Hadi Susilo Arifin; Regan Leonardus Kaswanto (Jurnal Ilmu Pertanian Indonesia, 2023)
The concept of "Stingless Bee-Friendly Local Home Garden" can be an alternative for urban landscape conservation through home gardens, especially in Depok City, which has a rapid flow of development. For this reason, a management strategy is needed as part of an effort to improve the landscape services of Depok City. This study aims to analyze the characteristics of home gardens and the potential for developing stingless bee-friendly home gardens to support the optimization of urban landscape services. The research was conducted using a field survey on sample of home gardens selected through purposive sampling methods, interviews, questionnaires, and literature studies. Based on the conditions of climate, weather, ecology, 90 samples of home gardens and respondents, Depok City has the potential to develop the concept of a honey bee-friendly home garden. These conditions can support the activity of stingless bees and provide a source of available food throughout the year. The concept of a stingless bee-friendly home garden can be achieved by presenting a diversity of food plant sources, providing bee hives, and proper home garden management. Therefore, it is necessary to conduct socialization and training on stingless-bee keeping in the yard starting from farmers group, making an example of a honey bee-friendly home garden, and increasing green space connections in the city Keywords: home garden management, landscape services, stingless bee-friendly home garden, urban landscape